Il Museo di Storia Naturale dell'Università degli Studi di Firenze VOL. 1 LE COLLEZIONI DELLA SPECOLA Le collezioni della Specola: zoologia e cere anatomiche | The Collections of La Specola: Zoology and Anatomical Waxes - BARSANTI, GIULIO; Chelazzi, Guido (Cataloghi e collezioni, 2009)
The Museum of Natural History of the University of Florence, founded in 1775 by the Grand Duke Peter Leopold, is the oldest scientific museum in Europe. Firenze University Press opens the series dealing with the six sections of the Museum with this book on La Specola, situated in Palazzo Torrigiani, which represented the original nucleus. The articles in the first section reconstruct the historic background, the foundation of La Specola and the genesis and development of the collections. The second part considers the anatomical waxes, the entomological collections, and those of the vertebrates and the invertebrates, with a view to providing a description of the precious specimens that is at once precise and accessible. Finally, the third section completes the picture, retracing the important research activity that has accompanied the history of La Specola and reporting on the scientific projects in which the personnel are engaged. The largest collection in the world of anatomical wax models and the vast zoological collection are illustrated by the people directly involved in the related research, and by a superb selection of original photos produced specially for this publication.